PENGARUH LITERASI DIGITAL DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN IPS - Kharisma Ramadhani; Abd. Ghofur; Kuswanto (Jurnal Genta Mulia, 2026)
This research aims to examine the influence of digital literacy and learning motivation on student learning outcomes. The method used is quantitative. The sample taken consisted of 50 class VIII students at MTs Miftahul Jinan Dlanggu, who were selected using a saturated sampling technique. To collect data, various instruments were used, including questionnaires, observations, tests and documentation. The data obtained was analyzed by carrying out normality tests, multiple linear regression tests, and hypothesis testing. Based on the results of the analysis, digital literacy has a positive and significant influence on student learning outcomes. Apart from that, learning motivation also shows a significant and positive influence on learning outcomes. Simultaneous analysis reveals that digital literacy and learning motivation simultaneously have a positive impact on student learning outcomes. Overall, this research confirms that digital literacy and learning motivation play an essential role in facilitating students to achieve satisfactory learning outcomes, so they are factors that need to be considered in the educational process.